Specificity of Understanding of Deception at Presenile and Senile Age - Melehin, A. (Psihologiâ i pravo, 2019)
The article shows that since the age of 61-74, partial changes are observed in the understanding of deception with a predominance of an emotional-egocentric shift. There are no difficulties in understanding the social situation and the ability to draw conclusions about the false beliefs of only one person (“first-order” representations). At presenile (61-74 years) and senile (75-90 years) age, there is a shortage of representations of the "second" order of the mental model. The phenomenon of denial of socio-cognitive changes or specific cognitive anosognosia (i.e. most people at senile age do not notice a change in understanding of fraud) is described. General predictors of the deception understanding are highlighted: socio-demographic (level of education) and psychological (symptoms of depression, solitude, satisfaction with the quality of life, subjective age) as well was age-specific predictors: changes in family, work status, cognitive functioning and polymorbidity. В статье показано, что начиная с 61—74 лет у человека наблюдаются парциальные изменения в понимании обмана с преобладанием эмоционально-эгоцентрического сдвига. Отсутствуют трудности в понимании социальной ситуации и способности делать выводы о ложных убеждениях только одного человека (репрезентации «первого» порядка). В пожилом (61—74 лет) и старческом (75—90 лет) возрастах наблюдается дефицит репрезентаций «второго» порядка модели психического. Описан феномен отрицания социокогнитивных изменений или специфической когнитивной анозогнозии, т. е. большинство людей позднего возраста не замечают изменения в понимании обмана. Выделены общие предикторы понимания обмана: социодемографические (уровень образования) и психологические (симптомы депрессии, чувство одиночества, удовлетворенность качеством жизни, субъективный возраст). Также выделены возрастно-специфические предикторы: изменения в семейном, рабочем статусе, когнитивном функционировании и полиморбидность.